Offline Handwritten Signature Watermark For Digital Document Authentication - Yaw, Low Cheng (2008)
This thesis introduces a novel biometric watermarking technique using offline handwritten signature, namely, signature image, as the watermark. Traditionally, the host image is embedded using originator's name, graphical logo and serial number which can easily be forged. Biometric watermarking, which synergistically integrates biometrics and the digital watermarking technology, is therefore proposed to replace the traditional digital watermarking techniques. The primary advantage of the offline handwritten is that it is a type of biometric behavioral attribute possessing unique means to identify an individually unambiguously.